Pengaruh Diskon, Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di Swalayan Diva Kabupaten Kediri - Alvianto Nuha Syairul Anam; Miftahul Munir; Angga Permana Mahaputra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The influence of market trader service quality, which consist of the variables direct evidence, realibility, responsiveness, assurance and empathy, in very important to know how much influence it has on purchasing decisions at supermarkets. Diva can estimate how the community responds and improves the quality of services provided in the future. The sampling technique in this research uses the probability sampling method. Meanwhile the samples taken were obtained through questionnaires, observations and interviews. The service result have a significant influence on purchasing decisions.